1980
DOI: 10.1002/ijc.2910250409
|View full text |Cite
|
Sign up to set email alerts
|

In vivo natural reactivity of mice against tumor cells

Abstract: A rapid in vivo clearance of tumor cells was found in normal mice following intravenous inoculation of [125l]dUrd‐labelled YAC‐1 and RBL‐5 cultured cell lines derived from lymphomas. The ability of mice to eliminate tumor cells from spleen, liver and lungs during the first 4 h, as evaluated by the recovery of radioactivity in these organs, was found to correlate with the level of natural killer (NK) cell reactivity in their spleen and lungs, as measured simultaneously in vitro in a shortterm 51Cr release assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 43 publications
8
65
2
Order By: Relevance
“…Laboratory Investigation • December 2002 • Volume 82 • Number 12 supports the antitumor effects of NK cells in animal models (Barlozzari et al, 1985;Gorelik et al, 1982) and in humans (Coca et al, 1997;Riccardi et al, 1980;Tartter et al, 1987;van Duinen et al, 1988;Whiteside and Herberman, 1994). For instance, Blom et al (1997) demonstrated that down-regulation of HLA-A expres- …”
Section: Hla-i and Prognosis In Colorectal Cancermentioning
confidence: 91%
“…Laboratory Investigation • December 2002 • Volume 82 • Number 12 supports the antitumor effects of NK cells in animal models (Barlozzari et al, 1985;Gorelik et al, 1982) and in humans (Coca et al, 1997;Riccardi et al, 1980;Tartter et al, 1987;van Duinen et al, 1988;Whiteside and Herberman, 1994). For instance, Blom et al (1997) demonstrated that down-regulation of HLA-A expres- …”
Section: Hla-i and Prognosis In Colorectal Cancermentioning
confidence: 91%
“…It may be that the 3E clone represents a non-tumorigenic subpopulation within the EJ line, or alternatively the 3E clone induced a host immune response. Although the nude mice lack functional T cells, they do have natural killer (NK) and natural-cytotoxic (NC) cells, which are capable of immumnological surveillance (Herberman, 1980;Riccardi et al, 1980;Warner et al, 1977). As the 3E clone was found to produce tumour nodules in immunodeficient hosts, some of which then regressed, the possibility that the 3E clone elicits a natural immune response from the host is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…NK CELL-MEDIATED ANTITUMOR MECHANISMS NK cells originally described as large granular lymphocytes, exhibited natural cytotoxicity against certain tumor cells in the absence of preimmunization or stimulation. [35][36][37] CD56 dim NK cells, which make up the majority of circulating cells, are the most potent cytotoxic NK cells against tumor cells. Evidence gathered from a mouse xenograft tumor model testing functionally deficient NK cells or antibody-mediated NK cell depletion supports that NK cells can eradicate tumor cells.…”
Section: Conception Of Nk Cellsmentioning
confidence: 99%